Impingement Cooling Using the Ionic Wind Generated by a Low-Voltage Piezoelectric Transformer - Johnson, Michael J.; Go, David B. (Frontiers in Mechanical Engineering, 2016)
As the consumer demand for smaller, more sophisticated computers grows, the need arises for new air cooling methods that will work in geometries that mechanical fans cannot. Ionic winds (also known as electrohydrodynamic flows) are flows that are produced by the generation of a gas discharge. These flows do not require moving parts to operate, making them attractive for small form factor devices. However, in order to produce and sustain a gas discharge in atmospheric air, very large applied voltages are required ( 5 kV). Through the use of piezoelectric transformers (PTs), it is possible to generate ionic winds in ambient air with significantly smaller voltages ( 7 V) than otherwise possible. When a moderate voltage is applied to a piezoelectric transformer (PT), discharges can form on the edges of the crystal that produce measureable ionic winds. The impingement cooling properties of these ionic winds jets on a vertical, uniformly-heated metal plate were studied by measuring their induced forced convection coefficients. Using a sharpened piezoelectric crystal, a round, axis symmetric ionic wind jet was formed, and it followed similar heat transfer correlations to that of more conventional jets. The sharpened piezoelectric was able to produce convection coefficients near 50 W m-2 K-1 under the right conditions. When the piezoelectric was not sharpened, the piezoelectric transformer produced similar convection coefficients, but cooled a larger area than its counterpart, as ionic wind jets were generated off the corners of the rectangular device.